FAKTOR-FAKTOR YANG MEMPENGARUHI CAPITAL STRUCTURE PADA CONSUMER NON-CYCLICALS DAN CYCLICALS - Cudivia, Vania Griselda; Salim, Susanto; Daryatno, Andreas Bambang (Jurnal Paradigma Akuntansi, 2025)
This research aims to examine the factors that influence capital structure in consumer non- cyclicals and consumer cyclicals companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. Factors that determine the capital structure include profitability, liquidity, tangibility and firm size. Sample was selected using purposive sampling method and the valid data was 17 companies. Data processing techniques using descriptive multiple correlation coefficient analysis, determination coefficient analysis, multiple linear regression test, F-test and t-test that helped by IBM SPSS statistics 27. Based on the results of simultaneous research tests, it shows that the variables profitability, liquidity, tangibility and firm size together have a significant influence on capital structure. Based on the results of the partial test research, it shows that the profitability and liquidity variables individually have a significant negative effect on capital structure, while tangibility and firm size individually have an insignificant negative effect on capital structure.